The Psychotherapeutic Technique «Family Chest» with the Psychological Support of Families that Have Problem Children - Mushkevych, Myroslava (Psychological Prospects Journal, 2020)
The article presents the results of using the Family Chest technique in the process of psychological support of the psychotherapeutic technique. Methods. The main approaches to the use of psychotechnique are described, in the implementation of which the client is offered to present the image of a family chest, assuming that the description will present unconscious family and personal needs, conflicts or affects that form the content of the unconscious. It is indicated that the images are associated with the unconscious, are quite universal and have the status of archetypal images, correlated with existential life situations. Results. It is generalized that in the experimental group, as a result of introducing the technique at the stage of the control diagnostic section, the frequency of expression of the positive modality of all certain empirical indicators is significantly higher than the frequency of expression of it in the control group. It is evidenced that among the representatives of the experimental sample, the number of family members with problem children with the prevailing attitude toward a positive perception and acceptance of a partner or other members of the nuclear family, with a reflexive attitude and readiness to generate a constructive space for marital and family relationships, cultivation of «healthy» family values ​​and attitudes, with the implementation of constructive role-playing patterns of family functioning, turned out to be higher than among representatives of the control sample. It was highlighted that the level of formation of a personal attitude towards a positive perception and acceptance of a partner or other members of the nuclear family, among members of families with problem children, as part of the introduction of psychotherapeutic techniques, is 4,5 times higher. Conclusions. It has been proved that an important component of psychological support for families with problem children is the psychotherapeutic phase using the Family Chest psychotechnique aimed at developing positive changes in relation to family values, family roles, family attitudes, characteristics of spousal and family relationships, adoption of a partner or other members of the nuclear family that have become targets of psychological support. It is noted that promising areas for further research are improving the program of psychological support for families with problem children, drawing up empirical diagnostic programs for the formation of the content of psychological support for families using effective psychotherapeutic techniques.